Algumas contribuições do paradigma de escolha para o trabalho de pessoas com deficiência intelectual - Escobal, Giovana (Universidade Federal de São Carlos, 2010)
For the Analysis of Operant Behavior, between behavior and choice there is a bidirectional relationship, because each environmental stimulus has the potential to control various responses and the repertoires of individuals are complex. The selection of the response to be emited before each stimulus in each context constitutes in a condition of choice. The choice behavior is typically studied by concurrent schedules and chain concurrent schedules of reinforcement, and practical applications of the experimental model have been increasingly frequent. The present study aimed to investigatie the choice of adults with intellectual disabilities under work conditions; assess the preference for work components and to evaluate the influence of the situation of choice and no choice on parameters performance in such conditions. Four individuals have learned a task, with and without environmental work support. The work task was to assemble notebook s cover by gluing pieces of paper on the background cover. The arrangement developed for the work task, contained devices for placement of shredded paper, background covers and glue. Its goal was to provide immediate assistance to increase or maintain the frequency of the behavior and prevent errors in routine task. Then, the chain concurrent schedules of reinforcement were introduced. The participant could choose, in the first link, pressing a button on a fixed ratio schedules (FR 1), the condition, with or without environmental work support, with which would work on the second link. In Phase 2, participants could choose, still pressing a button and under fixed ratio schedules (FR1) among multiple schedules of reinforcement, without choice, and concurrent chain schedules of reinforcement, with choice. In multiple schedules, the components alternated in an almost random manner and differed in relation to the presence or absence of environmental work support. The criterion for response stability for parameters performance in relation to time and number of errors, respectively, was maximum variation of a minute around the average for the time parameter and a maximum variation of one error around the average for the number of errors parameter, both for three consecutive trials. The criterion for stability of the choice response was to emit at least 12 choices in the initial link of the chain concurrent schedules and emission of 100% of choice responses in the initial links of the chain concurrent schedules with a preference for one of the alternatives with or without environmental work support and with and without choice in four trials (one session) in two consecutive sessions. The performance under multiple schedules, without choice of component, was compared with performance under concurrent schedules, in which participants could choose the alternative that would work to verify the function of choice on performance in the alternatives, with and without environmental work support. In the teaching phase, participants learned the six steps of the task and showed a higher amount of instructions without the environmental work support. Both in the teaching phase and in Phases 1, 2, 3 e 4, all participants completed the task, on average, faster in the presence of the environmental work support. The condition with environmental work support and the alternative with choice proved to be preferable from the point of view of the individual with intellectual disabilities. Moreover, in general, working in the presence of the condition of choice, the participants completed the task with lower average of total time, and kept the number of errors in low level. Choice was made, therefore, without prejudice to its performance in the parameters analyzed. The study contributes to the development of professional training programs of individuals with intellectual disabilities, and brings important practical implications for planning education for this population.
Keywords: Escolha (Psicologia); Preferência; Trabalho; Esquemas concorrentes; Deficiência intelectual; Esquemas múltiplos; Trabalho; Indivíduos com deficiência intelectual; Arranjo instrucional; Choice; Preference; Multiple schedules; Chain concurrent schedules; Work; Individuals with intellectual disabilities; Environmental work support; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL